2022
DOI: 10.1002/aenm.202202219
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics‐Boosted Effect Enabled by Zwitterionic Hydrogel Electrolyte for Highly Reversible Zinc Anode in Zinc‐Ion Hybrid Micro‐Supercapacitors

Abstract: Despite impressive merits of complementary charge‐storage mechanisms for aqueous Zn‐ion hybrid micro‐supercapacitors (ZHMSCs), it remains a challenge to solve dendrite and parasitic reactions issues of Zn anodes. Herein, a kinetics‐boosted strategy of Zn2+ transport and desolvation of hydrated Zn2+ is proposed by engineering zwitterionic P(AM‐co‐SBMA) hydrogel electrolyte (PASHE) for highly reversible Zn plating/stripping. Mechanically robust and chemically anchored PASHE features zwitterionic groups for const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 73 publications
1
63
0
Order By: Relevance
“…Additionally, new signals located at 1241, 1161, 1030, and 637 cm −1 can be detected, which correspond to the symmetric CF 3 stretching vibration, asymmetric CF 3 stretching vibration, symmetric SO 3 stretching vibration, and asymmetric SO 3 bending of CF 3 SO 3 − anion, respectively. 34–36 The obtained results suggested that the SPS–Zn hydrogel electrolyte was successfully synthesized.…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, new signals located at 1241, 1161, 1030, and 637 cm −1 can be detected, which correspond to the symmetric CF 3 stretching vibration, asymmetric CF 3 stretching vibration, symmetric SO 3 stretching vibration, and asymmetric SO 3 bending of CF 3 SO 3 − anion, respectively. 34–36 The obtained results suggested that the SPS–Zn hydrogel electrolyte was successfully synthesized.…”
Section: Resultsmentioning
confidence: 85%
“…[16][17][18][19][20] In particular, their capability to function more effectively in terms of suppressing the growth of Zn-dendrites and undesirable side reactions compared to liquid electrolytes is mainly attributed to the less reactive free water and the robust coordination interaction between Zn 2+ and functional groups in HEs. 17,21,22 Unfortunately, the development of quasi-solid-state ZICs has been hindered by severe interfacial issues. During deep cycling, the mismatch between the static quasi-solid electrolyte surface and the dynamic Zn anode volume change originating from uneven ion diffusion and deposition will lead to inferior interfacial contact, ultimately resulting in a premature failure of the ZICs.…”
Section: Introductionmentioning
confidence: 99%
“…42 Zwitterions or 'inner salts' represent a unique class of small molecules in which cationic and anionic species are covalently bound, which have been proven to address the key roadblock in electrochemical devices. 22,26,[43][44][45][46][47] For example, Archer et al found that zwitterionic moieties were capable of tuning the Li + -solvation environment at the electrode/electrolyte interface, enabling the compact, planar deposition of lithium metal. 44 Besides, Pringle et al demonstrated that zwitterion-based electrolytes enabled high target ion transport and supported stable lithium metal cell cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage gaps of Zn/SPSF/Ti and Zn/PMIA/Ti cells increase gradually as the number of cycles increases, which confirmed the continuous growth of zinc dendrites. 45,46 Impressively, the Zn/SP/Ti cell not only exhibits a high initial CE of 94.1% and low voltage hysteresis (69.8 mV), but also a significant improvement in cycle life, maintaining a stable voltage gap after 400 cycles. The CEs of Zn–Ti half-cells are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%